Communications Newsletters and Extension: A Survey - Mary F. Laurent (Journal of Applied Communications, 1985)
Good communication skills are essential in any business. They are becoming increasingly important to the mission of the Extension Service. One way to foster development and growth of these skills is with a communications newsletter. This is the story behind the resurrection of a communications newsletter for Extension agents and specialists at the University of Kentucky.